Simulation of performance on multi-quantum-well violet InGaN laser diode and analysis of its output for digital modulation - Abdullah, Rafid A. (2010)
This simulation and theoretical study is divided into two parts. Part one focuses on the performance of multi-quantum-well (MQW) violet InGaN laser diode (LD); whereas, part two focuses on the analysis of the output of this laser for the purpose of digital modulation. Two programs have been utilized. They are ISE TCAD (Integrated System Engineering Technology Computer Aided Design) simulator and MATLAB program. The researcher has coupled ISE TCAD simulator with MATLAB program as a new method for the purpose of simulation of digital modulation of the LD. The main objectives of this study are to obtain a low threshold current and kink-free light output power-current (L-I) curve of the MQW violet InGaN LD with an emission wavelength near 405 nm, and to analyse the output of the LD for the purpose of digital modulation.